Pengaruh Model Pembelajaran Osborn Terhadap Kemampuan Berpikir Kreatif Siswa SMAN 2 Jember - Karina Cindy Cahyadewi; Pambudi, Didik Sugeng; Murtikusuma, Randi Pratama; Sugiarti, Titik; Oktavianingtyas, Ervin (LPPM Universitas Advent Indonesia, 2024)
Creative thinking is the ability that every person has to come up with new thoughts and look at problems from various points of view, so that various solutions are obtained to solve a problem. In the Merdeka Belajar curriculum, which has now been implemented at various levels of education, creative thinking is one aspect of the assessment. The aim of this research is to examine the influence of the Osborn learning model on students' ability to think creatively at SMAN 2 Jember on quadratic function material. This research was carried out experimentally and was designed based on quasi experimental research. The design form of this research is a nonequivalent control-group design with data collection methods by applying methods in the form of written tests, documentation and observation. The samples involved were two classes chosen randomly after it was stated that the mathematical abilities of all class X were homogeneous. The two classes are class X.8 and class X.10. Class X.8 as an experimental class implements the Osborn learning model, while class X.10 as a control class implements conventional learning. The data analysis used is the prerequisite tests including normality and homogeneity tests, Independent Sample T-Test or Mann-Whitney test, Right Side T-test, and N-Gain test. Based on these statistical tests, it was concluded that implementing the Osborn learning model in the experimental class had a more significant and positive effect on creative thinking abilities.